Our Predicament, Our Prospects - Berman, Russell A. (The German quarterly, 2000)
"A collection of thoughts on the current state and future of the study of German in the United States". Russell A. Berman "identifies the twin predicaments of declining enrollments and challenging methodological debates, and points to the prospects for cultural transfer, language learning, teaching literature, and the revival of cultural studies". Sara Friedrichsmeyer "notes the lack of consensus over disciplinary identity for US German scholars, and suggests a greater acknowledgment and discussion of beauty in literary texts in response". Sander L. Gilman 'traces changes over the last thirty years of the study of "things German," and stresses the enduring relevance of the German past'. Sara Lennox "finds the answers to fundamental questions for German Studies - its purpose and justification - in the ideological struggles found in German cultural studies as practiced in the US". Elizabeth Loentz "shares her views on pragmatic measures to keep German Studies vital, from the perspective of a scholar newly entering the professoriate". John Long "discusses the future and impact of German Studies in low-income and minority communities". Paul Michael Lützeler "discusses the need to combine culture studies, language learning, and the Humanities in today's German Studies". Siegfried Mews "calls for renewed attention to the fundamental core, teaching Germanic languages, literatures, and cultures". John A. McCarthy "proposes defining the center of" Germanistik "in the embrace of change and interdisciplinarity, drawing on the energies which produced literary texts under study in the first place". Jeffrey M. Peck "sees benefits to extending the internationalization of German Studies through contemporary global political and economic issues". James Rolleston "reminds us of the contradictions inherent in conceiving a discipline that places its practitioners simultaneously both inside and outside itself, and its subject matter". Lynne Tatlock "provides a sobering assessment of some problems facing the discipline and the profession".